ANALYSIS OF INFLUENCING FACTORS TENDENCY OF EMPLOYEES TO DO FRAUD IN THE GOVERNMENT SECTOR (CASE STUDY OPD IN KUANTAN SINGINGI REGENCY) (Program Studi Akuntansi - Universitas Islam Kuantan Singingi, 2020)
Abstract This research was conducted at the Regional Apparatus Organization (OPD) in Kuantan Singing Regency. This study aims to determine the factors that influence the tendency of employees to commit fraud / cheating in the government sector. The main problems that will arise, the researcher will be as follows: To see the size and significance of the influence between the dependent variable and the independent variable. The type of data used in this research is primary data, namely data that comes from the source, then the data technique uses the sampling method purposive sampling namely the technique of taking samples with certain considerations. This research is included in quantitative research. There were 78 respondents consisting of the head of the financial division and financial staff in each OPD in Kuantan Singingi Regency. This data was analyzed using multiple regression with SPSS Version 21. The results of this study indicate that the pressure has an effect on fraud in the Government Sector of Kuantan Singingi Regency with a significant value (0.023) and the value of t count (2.328), opportunities don't effect on fraud in the Government Sector of Kuantan Singingi Regency with a significant value (0,528), and the value of t count (-0,634), and justification effect on fraud in the Government Sector of Kuantan Singingi Regency with a significant value (0.018), and the value of t count (2,413). So that the conclusions of this study are 2 hypotheses which is presented can be accepted and 1 hypothesis is rejected. Keywords: Fraud (Pressure, Opportunity, Rationalization) ABSTRAK Penelitian ini dilakukan pada Organisasi Perangkat Daerah (OPD) yang ada di Kabupaten kuantan singing.Penelitian ini bertujuan untuk mengetahui fator-faktor yang mempengaruhi kecendrungan pegawai melakukan kecurangan/fraud pada sektor pemerintahan. Pokok permasalahan utama yang akan dijelaskan peneliti adalah sebagai berikut: Untuk melihat seberapa besar pengaruh dan signifikan antara variabel dependen dengan variabel independen. Jenis data yang digunakan dalam penelitian ini adalah data primer yaitu data yang berasal dari sumbernya, selanjutnya dalam teknik pengumpulan datanya, pengambilan sampel dilakukan dengan metode purposive sampling yaitu teknik pengumpulan sampel dengan pertimbangan tertentu. Peneitian ini termasuk dalam penelitian kuantitatif.Respondennya sebanyak 78 yang terdiri dari kasubag keuangan dan staf pegawai keuangan di setiap OPD yang ada di Kabupaten Kuantan Singingi.Data ini dianalisis menggunakan regresi berganda dengan SPSS Versi 21. Hasil penelitian ini menunjukkan bahwa tekanan berpengaruh terhadap kecurangan di Sektor Pemerintahan Kabupaten Kuantan Singingi dengan nilai signifikan (0.023) dan nilai t hitung (2.328), peluang tidak berpengaruh terhadap kecurangan di Sektor Pemerintahan Kabupaten Kuantan Singingi dengan nilai signifikan (0,528) dan nilai t hitung (-0,634), dan pembenaran berpengaruh terhadap kecurangan di Sektor Pemerintahan Kabupaten Kuantan Singingi dengan nilai signifikan (0.018) dan nilai t hitung (2,413). Sehingga kesimpulan dari penelitian ini adalah 2 hipotesis yang di sajikan dapat diterima dan 1 hipotesis ditolak. Kata kunci :Fraud (Tekanan, Peluang, Pembenaran)